Complete gallbladder torsion diagnosed with sequential computed tomography scans: a case report - Koyanagi, Takahiro (BioMed Central, 2012)
INTRODUCTION: Torsion of the gallbladder is an extremely rare cause of acute abdomen, which commonly affects thin elderly women. A prompt surgical approach is necessary to avoid fatal complications associated with gangrene and perforation of the gallbladder. However, it is difficult to make a preoperative diagnosis using ordinary imaging modalities. CASE PRESENTATION: An 84-year-old Japanese woman was admitted to our hospital due to left lower abdominal pain. Her pain shifted suddenly to the right upper abdomen a half day after admission. Although her enlarged and wall-thickened gallbladder had been already seen at admission, it rotated approximately 180 degrees and deviated to the midline of her abdomen on the second computed tomography scan, which helped us to make a correct diagnosis of gallbladder torsion. The patient underwent an emergency operation (detorsion and cholecystectomy) and recovered without any complications. The gallbladder had necrosis due to torsion. CONCLUSION: Sequential diagnostic imaging might be helpful to make a preoperative diagnosis of gallbladder torsion when the gallbladder is enlarged and wall thickened but the patient does not present with typical clinical symptoms.